Pomen in uporaba specialnega testiranja v borilnih športih - Gorše, Luka (Šport (Ljubljana), 2014)
In this article we will describe the meaning and problems of special testing in combat sports and present current situation. We will explain why testing is important for planning and supervision of training process and for identification of physical preparedness and competition performance. We will stress the importance of special testing in combat sports and problems when depending on laboratory testing such as isokinetic dynamometer or cyclic ergometer. Hereinafter we will list which types of special tests do we know, describe each type and present at least one useful example of test or test battery which coaches or athletes of striking or grappling combat sports can use in their training or competition process.
Keywords: borilne veščine; borilni športi; combat sports; martial arts; norme; norms; special testing; specialno testiranje; sport; šport; športna dejavnost; testing; testiranje; training process; vadbeni proces